An examination of the benefit of the Sexual Assault Care and Practice (SACP) Programme in Gauteng, South Africa - Mooideen, Claire (My University, 2012)
In the reflective section of this paper I show that healthcare for gender-based violence, especially sexual assault patients has largely been a neglected area of service delivery in South Africa. There are substantial gaps in service provision in many parts of the country with repeated reports that the process of seeking health care and justice exposes such patients to further trauma. I suggest that in South Africa, as well as elsewhere, it is time for nursing to take the lead in building multidisciplinary partnerships in clinical practice, education, and research in the area of sexual assault and violence. It shows why it is imperative that the underlying intention of upholding and promoting patient advocacy and family health care remains a core value of nursing. It argues that the role of “forensic skill and knowledge” in the nursing sector is vital tool in the struggle against gender-based violence. In the empirical section, a survey was conducted to examine and articulate the question of the Sexual Assault Care and Practice (SACP) programme being a benefit (or not) to Sexual assault caregivers; to determine whether there has been retention of the knowledge by nurses and doctors who participated in the SACP programme; to evaluate whether there is or is not an improvement in service provision for sexual assault clients, to evaluate if the participants felt the SACP programme to have been of benefit and to identify hindrances to programme implementation. As noted by this study, survivors of sexual assault and violence continue to be in need of expert forensic services, and knowledge concerning the management and care of survivors appears to benefit from a formal training programme. No determination could be made from this survey concerning the perceived benefits of the programme or hindrances to care. This may reflect the current status of the programme in South Africa and provides cause for reflection.
Keywords: Sexual Offenses